2006
DOI: 10.1093/ndt/gfl360
|View full text |Cite
|
Sign up to set email alerts
|

Induction and long-term treatment with cyclosporine in membranous nephropathy with the nephrotic syndrome

Abstract: This study suggests that 12-month therapy with CyA (+/-prednisolone) is effective in inducing remission in most nephrotic patients with MN and well-preserved renal function. Longer treatment with lower doses is a useful approach to maintain remission. Relapses occur more frequently in the monotherapy group and usually are associated with CyA trough levels<100 ng/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 14 publications
3
54
0
2
Order By: Relevance
“…High rates of relapses were noted in most studies with sufficient follow-up duration (Table 3). In the study of Alexopoulos et al, it was suggested that combination therapy with CsA and steroids is more effective in inducing remission and preventing relapses as compared with CsA monotherapy [60]. In this study, 31 patients were treated with a combination of CsA and prednisone and 20 with CsA monotherapy.…”
Section: Treatmentmentioning
confidence: 88%
“…High rates of relapses were noted in most studies with sufficient follow-up duration (Table 3). In the study of Alexopoulos et al, it was suggested that combination therapy with CsA and steroids is more effective in inducing remission and preventing relapses as compared with CsA monotherapy [60]. In this study, 31 patients were treated with a combination of CsA and prednisone and 20 with CsA monotherapy.…”
Section: Treatmentmentioning
confidence: 88%
“…On the other hand, if after 3 to 4 mo of CsA therapy at adequate doses proteinuria is not significantly reduced, then it is unlikely that the therapy will be effective. Prolonged low-dose CsA (approximately 1.5 mg/kg per d) could be considered for long-term maintenance of patients with preserved renal function who achieve CR or PR but who relapse once CsA is discontinued, with little risk for nephrotoxicity (55).…”
Section: Immunosuppressive Therapymentioning
confidence: 99%
“…In these patients, prospective randomized clinical trials have demonstrated that the calcineurin inhibitors (CNIs) cyclosporine (5,6) and tacrolimus (7) induce complete or partial remission of proteinuria in more than 70% of patients. However, more than 60% of patients treated with CNI suffer subsequent relapses or become treatment dependent (5)(6)(7)(8) and need prolonged therapy to maintain remission, which exposes them to the nephrotoxic effects of this drugs. Consequently, for these patients, there is a need for the development of new treatment strategies aimed at reducing the risk of chronic nephrotoxicity.…”
mentioning
confidence: 99%